2002
DOI: 10.1177/0091270002042009005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Celecoxib and Diclofenac on Blood Pressure, Renal Function, and Vasoactive Prostanoids in Young and Elderly Subjects

Abstract: Cyclooxygenase (COX) inhibitors are among the most widely used drugs, especially in the elderly. It has been claimed that the new COX-2 inhibitors offer advantages in terms of drug safety. To test this hypothesis, the authors compared in a double-blind, randomized trial the effects of celecoxib (200 mg bid) and diclofenac (75 mg bid) on blood pressure and renal function in two groups (each n = 12) of young (mean age = 32 years) and elderly (mean age = 68 years) normotensive subjects. Changes from baseline in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
6

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 5 publications
3
19
0
6
Order By: Relevance
“…However, we observed a strong, but nonsignificant, trend toward reduction of urinary PGE-M excretion by celecoxib before (−14% in 24-hour urine and −34% in 2-hour urine) and after furosemide (−33%). In line with these results are the findings of Dilger et al [31], who reported a 35% reduction of urinary PGE-M excretion in young healthy volunteers treated for 15 days with celecoxib 200 mg twice a day. In contrast, the recently published study by Murphey et al [36] found a 62% reduction of urinary PGE-M excretion in healthy volunteers treated with rofecoxib 50 mg/day for 4 days.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, we observed a strong, but nonsignificant, trend toward reduction of urinary PGE-M excretion by celecoxib before (−14% in 24-hour urine and −34% in 2-hour urine) and after furosemide (−33%). In line with these results are the findings of Dilger et al [31], who reported a 35% reduction of urinary PGE-M excretion in young healthy volunteers treated for 15 days with celecoxib 200 mg twice a day. In contrast, the recently published study by Murphey et al [36] found a 62% reduction of urinary PGE-M excretion in healthy volunteers treated with rofecoxib 50 mg/day for 4 days.…”
Section: Discussionsupporting
confidence: 85%
“…Remarkably, in women older than 65 years with physiologic decline of renal function, sustained decreases of urinary PGE 2 excretion after administration of celecoxib 200 mg twice a day and naproxen 500 mg twice a day for 5 days were observed [30]. Two further studies which assessed the effect of flosulide [11] and celecoxib [31] on urinary PGE 2 excretion included male volunteers, resulting in high and varying PGE 2 excretion rates due to contamination of urine with seminal fluid. Similarly, the study by Kammerl et al [13] included male volunteers and reported only the combined excretion of PGE-M and PGE 2 .…”
Section: Discussionmentioning
confidence: 99%
“…COX expression and its relationship with blood pressure have been widely investigated and meta-analyses of these results have found that COX inhibitors elevate blood pressure (Pope et al 1993;Johnson et al 1994). This finding has not been supported by more recent studies (Catella-Lawson et al 1999;Dilger et al 2002;Gertz et al 2002), and in the study of Pope et al (1993) raised blood pressure was found only in those animals that were hypertensive before the administration of the inhibitors. The increase in COX-2 expression in the animals from the present rat model, coupled with their reduced blood pressure, would support a role for COX in blood pressure regulation.…”
Section: Nutritional Effectsmentioning
confidence: 96%
“…The NSA has to be replaced by paracetamol in case of deterioration of renal function. Even in elderly patients NSA can be recommended as fi rst-line therapy, as Dil-ger et al [27] could not show any deterioration in blood pressure and renal function compared with young subjects.…”
Section: Renal Colicmentioning
confidence: 99%